1909
DOI: 10.5962/bhl.title.11133
|View full text |Cite
|
Sign up to set email alerts
|

The Columella auris in Amphibia

Abstract: The following is a preliminary communication of the results ohtained by us in a study of the relations and connections of the sound-transinitting apparatus in certain American Urodeles.Since it is in the class Amphibia that a sound-transmitting apparatus first appears, a knowledge of the relations liere is of double value,-in aiding the interpretation of homologies in the lower forms (fishes), and in contributing toward the solution of the difficult questions surrounding the significance of the reptilian colui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1933
1933
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…These were recently reviewed by Mason (2007), and include the detection of body movement (put forth by Eiselt [1941]), the protection of the inner ear against intense sounds (put forth by Wever [1979Wever [ , 1985), enhancement of airborne sound perception (put forth by Lombard & Straughan [1974]), and, perhaps the most widely accepted function, detection of substrate-borne vibrations (put forth by Kingsbury & Reed [1909], and corroborated by experiments conducted by Hetherington [1985Hetherington [ , 1987Hetherington [ , 1988). Under the latter hypothesis, the muscular slip that connects the suprascapular cartilage of the shoulder girdle to the operculum of the middle ear transmits vibrations collected by the forelimbs to the ear.…”
Section: Reduction Of the Lagenar Maculamentioning
confidence: 99%
“…These were recently reviewed by Mason (2007), and include the detection of body movement (put forth by Eiselt [1941]), the protection of the inner ear against intense sounds (put forth by Wever [1979Wever [ , 1985), enhancement of airborne sound perception (put forth by Lombard & Straughan [1974]), and, perhaps the most widely accepted function, detection of substrate-borne vibrations (put forth by Kingsbury & Reed [1909], and corroborated by experiments conducted by Hetherington [1985Hetherington [ , 1987Hetherington [ , 1988). Under the latter hypothesis, the muscular slip that connects the suprascapular cartilage of the shoulder girdle to the operculum of the middle ear transmits vibrations collected by the forelimbs to the ear.…”
Section: Reduction Of the Lagenar Maculamentioning
confidence: 99%
“…In anurans, one end of the muscle is attached to the operculum and the other end is attached to the ventral surface of the suprascapular cartilage (BAKER, 1969;LOM-BARD and STRAUGHAN, 1974). An analogous mus-cular attachment to the operculum is present in many urodeles (KINGSBURY and REED, 1909;DUNN, 1941;MONATH, 1965;LOMBARD, 1971). Before considering the opercular apparatus in the anuran, let us briefly summarize the urodele middle ear.…”
Section: Opercularis Musclementioning
confidence: 99%
“…KINGSBURY and REED (1909) first suggested that the opercular apparatus serves to couple substrate vibrations from the ground via the pectoral limbs to the oval window. Thus the columella is involved in underwater hearing and the opercular muscle in terrestrial hearing.…”
Section: Opercularis Musclementioning
confidence: 99%
“…In the same letter he described the impoverished state of the colony, the loss of his winter clothes which he could not replace, and his desire for 'some beefe and some Cheese and butter'. 1 He also recorded his fear that the colonists' few provisions would soon be gone, stressing the importance of the expected arrival of the supply ship Seaflower. 2 Unbeknown to Frethorne, the Seaflower had been sunk in an accident two weeks earlier, and lay at the bottom of Southampton Harbor, Bermuda.…”
Section: Introductionmentioning
confidence: 97%